A Modest Proposal for Another Phenomenological Approach to Psychopathology - Mullen, Paul E. (Oxford University Press, 2007)
In 1912, Karl Jaspers published an article entitled “The Phenomenological Approach to Psychopathology.” This and his subsequent text, General Psychopathology, was to exert a profound influence on the development of psychiatry in general and psychiatric nosology in particular. The current Diagnostic and Statistical Manual of Mental Disorders and International Classification of Diseases both reflect, at least in part, that legacy. This article will argue that the descriptive psychopathology of Jaspers has been gradually transformed into a caricature which has substituted authority for enquiry and simplification for subtlety. We have been left with classificatory systems which impose reified categories increasingly at variance with clinical reality and increasingly divorced from the data generated by scientific enquiry. Returning to the phenomenological method, despite its contradictions, may open the way to clinical and research approaches which free us from the current straightjacket of orthodoxy which is impending our progress.